2014
DOI: 10.1051/kmae/2014026
|View full text |Cite
|
Sign up to set email alerts
|

Physical habitat and water chemistry changes induced by logging and gold mining in French Guiana streams

Abstract: Understanding the effects of disturbances on the physical-chemical quality of ecosystems is a crucial step to the development of ecosystem assessment tools. 95 sampling sites distributed among 4 categories of disturbance, i.e.: reference, logging, formerly and currently gold mining, were characterized using stream physical and chemical variables. Our hypotheses were: (i) logging and gold mining activities primarily affect the physical habitat structure of streams and (ii) both have an effect on chemical enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…This is of particular importance since damming, mining and logging are already known to affect the characteristics of Neotropical streams (de M erona, Vigouroux, & Tejerina-Garro, 2005;Dedieu et al, 2014;Dias et al, 2010), and are thus very likely to influence of both species richness and composition of stream fish assemblages. Moreover, the contribution of almost all the environmental descriptors of the local environment to both species richness and assemblage composition suggests that modifications to only a single component of the environment might alter fish assemblage composition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is of particular importance since damming, mining and logging are already known to affect the characteristics of Neotropical streams (de M erona, Vigouroux, & Tejerina-Garro, 2005;Dedieu et al, 2014;Dias et al, 2010), and are thus very likely to influence of both species richness and composition of stream fish assemblages. Moreover, the contribution of almost all the environmental descriptors of the local environment to both species richness and assemblage composition suggests that modifications to only a single component of the environment might alter fish assemblage composition.…”
Section: Resultsmentioning
confidence: 99%
“…This bias is probably due to the easier accessibility to lowland streams for sampling and to the limited commercial interest of the, often small-bodied, fishes inhabiting low-order streams compared to the large and heavily exploited downstream species (Allan et al, 2005). For instance, in French Guiana, more than 70% of the permanent river network is represented by streams <10 m wide (Dedieu, Allard, Vigouroux, Brosse, & C er eghino, 2014). For instance, in French Guiana, more than 70% of the permanent river network is represented by streams <10 m wide (Dedieu, Allard, Vigouroux, Brosse, & C er eghino, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We then analysed the impact of anthropogenic disturbances over the entire set of sampling sites, as in a previous study, we did not find any clear physical or chemical typology for these streams, but rather a continuum of environmental conditions (Dedieu et al 2014). Hence, according to Hermoso and Linke (2012), rather than analysing human impacts in different environmental types (type specific approach) we here preferred to use a continuum approach (or site specific approach) where we analysed human impacts on the taxonomic and functional composition of fish assemblages.…”
Section: Discussionmentioning
confidence: 97%
“…All the streams were less than 1 m deep, making the sampling sites comparable from an environmental point of view. Indeed, a previous study showed a continuum of environmental conditions but no clear typology within those Guianese streams (Dedieu et al 2014).…”
Section: Sampling Sitesmentioning
confidence: 88%